Financial and economic analysis of enterprises : a workers' education manual - Hedderwick, Karl.; International Labour Office (Geneva : International Labour Office, 1988)
This volume examines the layout and nature of company accounts and after discussing commercial, economic and financial aspects, introduces a practical and straightforward analytical model.
Includes index.
Bibliography: p. 133-135.
osc 28/01/2019
Loans
Keywords: Business enterprises; Corporations; Corporations